Introducing an Appropriate Geoportal Structure for Managing Wildlife Location Data - Mousavi, Zahra; Behzadi, Saeed (International Journal of Natural Sciences Research, 2019)
In recent years, access to spatial data, and also exchange them to achieve sustainable development in the country has been more and more in attention. Because with these spatial data and awareness of their existence, re-work and reproduction of data, the cost of time, and the cost to produce data are prevented. Environmental spatial data is one of the most important data that is very useful for planning and management. In this paper, we tried to show how to collect spatial information that is distributed in different organizations and databases, then we can provide this spatial information through geo-portal services based on managing wildlife. Knowing about the existence of such data and the ability to search and access them with a spatial geoportal, the user can have an important role in spatial data infrastructure. In addition, the user can make a decision that formed on environmental protection. Users can also search and access their spatial environment information with a geoportal if they exist. In addition, they will use spatial services of the layers. The spatial data is created in the form of standard spatial services, and is located in geo-portal to search and access to these layers. As a result, other organs can use these services or spatial data if necessary.